An in silico Approach for Integrating Phenotypic and Target‐based Approaches in Drug Discovery. Issue 1 (22nd October 2019) - Iwata, Hiroaki; Kojima, Ryosuke; Okuno, Yasushi
Abstract: Phenotypic and target‐based approaches are useful methods in drug discovery. The phenotypic approach is an experimental approach for evaluating the phenotypic response. The target‐based approach is a rational approach for screening drug candidates targeting a biomolecule that causes diseases. These approaches are widely used for drug discovery. However, two serious problems of target deconvolution and polypharmacology are encountered in these conventional experimental approaches. To overcome these two problems, we developed a new in silico method using a probabilistic framework. This method integrates both the phenotypic and target‐based approaches to estimate a relevant network from compound to phenotype. Our method can computationally execute target deconvolution considering polypharmacology and can provide keys for understanding the pathway and mechanism from compound to phenotype, thereby promoting drug discovery. Abstract :